2023
DOI: 10.1371/journal.pclm.0000236
|View full text |Cite
|
Sign up to set email alerts
|

Climate change, mental health, and reproductive decision-making: A systematic review

Hope Dillarstone,
Laura J. Brown,
Elaine C. Flores

Abstract: The impact of climate change on reproductive decision-making is becoming a significant issue, with anecdotal evidence indicating a growing number of people factoring their concerns about climate change into their childbearing plans. Although empirical research has explored climate change and its relationship to mental health, as well as the motivations behind reproductive decision-making independently, a gap in the literature remains that bridges these topics at their nexus. This review endeavours to fill this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…And it is possible that a change in values is taking place at a societal level, and that some young people simply want to have fewer or no children now, or in general (Guzzo & Hayford, 2023). A possible explanation for the decision to not have children is also concerns about climate change, but also economic or general insecurity could be further reasons (Danny, 2023;Dillarstone et al, 2023) The present study has several limitations. Firstly, it operates at the population level, which means that there is a lack of in-depth variables in the individual data.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…And it is possible that a change in values is taking place at a societal level, and that some young people simply want to have fewer or no children now, or in general (Guzzo & Hayford, 2023). A possible explanation for the decision to not have children is also concerns about climate change, but also economic or general insecurity could be further reasons (Danny, 2023;Dillarstone et al, 2023) The present study has several limitations. Firstly, it operates at the population level, which means that there is a lack of in-depth variables in the individual data.…”
Section: Discussionmentioning
confidence: 86%
“…It is possible that a change in values is taking place at a societal level, and that some young people simply want to have fewer children now, or in general (Guzzo & Hayford, 2023). A possible explanation for the decision to not have children is anxiety about climate change, also known as eco-anxiety, but also economic or general insecurity could be further reasons (Danny, 2023; Dillarstone et al, 2023)…”
Section: Discussionmentioning
confidence: 99%
“…There is actually little research on this topic, but it is obviously of great impact, as fewer people mean less GHG emissions. Dillarstone et al (2023) identified 13 relevant studies in the last decade, and summarized them as follows: Karis Climate change concerns were typically associated with less positive attitudes towards reproduction and a desire and/or intent for fewer children or none at all. Four themes explaining this relationship were identified: uncertainty about the future of an unborn child, environmentalist views centred on overpopulation and overconsumption, meeting family subsistence needs, and environmental and political sentiments.…”
Section: Geopolitical Strategic Complexitiesmentioning
confidence: 99%